The man who saved Kabuki : Faubion Bowers and theatre censorship in occupied Japan - Okamoto, Shirō, 1946- (Book collections on Project MUSE., 2001)
As part of its program to promote democracy in Japan after World War II, the American Occupation, headed by General Douglas MacArthur, undertook to enforce rigid censorship policies aimed at eliminating all traces of feudal thought in media and entertainment, including kabuki. Faubion Bowers (1917-1999), who served as personal aide and interpreter to MacArthur during the Occupation, was appalled by the censorship policies and anticipated the extinction of a great theatrical art. He used his position in the Occupation administration and his knowledge of Japanese theatre in his tireless campaign to save kabuki. Largely through Bowers's efforts, censorship of kabuki had for the most part been eliminated by the time he left Japan in 1948. Although Bowers is at the center of the story, this lively and skillfully adapted translation from the original Japanese treats a critical period in the long history of kabuki as it was affected by a single individual who had a commanding influence over it. It offers fascinating and little-known details about Occupation censorship politics and kabuki performance while providing yet another perspective on the history of an enduring Japanese art form. Read Bowers' impressions of Gen. MacArthur on the Japanese-American Veterans' Association website.